2015
DOI: 10.1016/j.jtcvs.2015.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Combined hypoxia inducible factor-1α and homogeneous endothelial progenitor cell therapy attenuates shunt flow–induced pulmonary arterial hypertension in rabbits

Abstract: Both the therapy with HIF-1α-transfected EPCs, and EPC transplantation, attenuated shunt flow-induced PAH, by means of an angiogenic effect. The former therapeutic method was more effective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Since HO activity appears to be necessary for EPC-mediated repair, this suggests that EPC therapy for PAH patients could be coupled to HO-1 induction using, e.g., EPO. This is further supported by recent evidence that EPC therapy is more efficient when HIF-1alpha, an inductor of HO-1-expression, is activated ( 50 ).…”
Section: Discussionsupporting
confidence: 55%
“…Since HO activity appears to be necessary for EPC-mediated repair, this suggests that EPC therapy for PAH patients could be coupled to HO-1 induction using, e.g., EPO. This is further supported by recent evidence that EPC therapy is more efficient when HIF-1alpha, an inductor of HO-1-expression, is activated ( 50 ).…”
Section: Discussionsupporting
confidence: 55%
“…Cell-based gene therapy has been found to be effective in preclinical models of PAH ( 5 , 6 ). Several studies have indicated that prepro calcitonin gene-related peptide (CGRP)-transfected EPCs, vascular endothelial growth factor-transfected EPCs, and hypoxia inducible factor 1α-transfected EPCs could effectively attenuate PAH and reverse pulmonary vascular remodeling ( 7 9 ). A PHACeT clinical trial reported that short-term hemodynamic improvement and the associated long-term benefits in functional and quality of life were evidenced in patients with PAH by delivering endothelial NO-synthase (eNOS) gene-enhanced EPCs ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxic–ischemic injury in stroke and myocardial infarction is well known with many stem cell treatments. Nowadays, combinations with different gene manipulations or drug preconditions in stem/progenitor cells are mostly used to study the therapeutic effect on in-vivo ischemic injury [ 40 42 ]. However, the concern of gene manipulation and its safety for transplanting cells are always raised in clinical trials.…”
Section: Discussionmentioning
confidence: 99%